Diborane(4)-metal bonding: between hydrogen bridges and frustrated oxidative addition - Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemical communications, 2012)
The metal complexes [M{HB(hpp)}2(CO)4] (M = Cr, Mo or W) and [M(cod){HB(hpp)}2Cl] (M = Rh or Ir) of the doubly-base stabilized diborane(4) ligand [HB(hpp)]2 were fully characterized and their bonding nature was investigated in detail. While bonding in the group 6 complexes predominantly occurs through the hydrogen atoms, the metal-ligand interaction in the group 9 complexes can be regarded as an early stage oxidative addition of the boron-boron bond leading to diboryl compounds.